School administrators' perceptions toward inclusion of children with special needs - Kuan, Yi-Kai (Ben) (Animo Repository, 2002)
The present study describes the perceptions of school administrators from regular schools with SPED classes and SPED schools on inclusion of children with special needs. Specifically, it looks into the profile of the school administrators in terms of age, gender, civil status, educational attainment and length of service. This study also determined if there is a significant difference on the school administrators' perceptions regarding inclusion of students with special needs. The researcher employed the descriptive method utilizing a questionnaire which consisted of two parts: personal information from the respondents and 48 close-ended type of questions about inclusion. Participants were sixty-six (66) school administrators from twenty-two (22) schools in Metro Manila - thirty-six (36) of them were from regular schools with SPED classes, while the other thirty (30) were from SPED schools.Findings indicate that majority of the respondents from both regular and special education schools are aged between 51 to 60 years old, are female, and are married. Majority of the respondents from regular schools with SPED classes have obtained a Master's degree, while majority of the respondents from special education schools have earned units for a Master's degree. Majority of the respondents from regular schools with SPED classes have served longer as school administrators than the respondents of special education schools. Both groups of school administrators appear to be generally in having positive perceptions on inclusion of children with special needs. It also found out that there is no significant difference on the means scores of the inclusion perceptions responses among school administrators.